Quantitative study of some trace elements and blood parameters in the third trimester of Iraqi pregnant women with Pre-eclampsia - Salih, Lina A.; Mahmood, Mahmood B. (Iraqi Journal of Science, 2022)
Pre-eclampsia complicates 2-8% of all pregnancies and it is one of the leading causes of maternal mortality and pre-term delivery in the world. Unfortunately, there is scarcity of documents discussing the circulating level of several essential trace elements in Pre-eclampsia patients in Baghdad especially in the last trimester of the pregnancy. The present study was designed to quantitative evaluation the whole blood concentration of two trace elements, copper (Cu), and iron(Fe), in pre-eclamptic women in the third trimester of pregnancy. The study was conducted on 18 Pre-eclamptic pregnant women as patients group with clinical detected high blood pressure ≥140/90 mmHg and 13 normotensive pregnant women as control group from Al-Alwiya for obstetric and gynecological hospital, clinical data were collected at routine obstetric visits. Hemoglobin (Hb) ,Packed cell volume (pcv) and measurements of 2 trace elements concentrations were measured in the whole blood of both patients and control group. Hematological parameters measurements explored non-significant differences was found in Hb value and pcv between the patients and the control group, although their mean levels were increased in the patients compared to the control group. According to the statistical analysis it was noticed there was non-significant differences (P>0.05) was found in the concentration of the copper between patients and control group. But significant (P<0.05) elevated concentration of Fe was conducted in the pre-eclamptic patients compared to the control. In conclusion, our study suggest that pre-eclampsia in the third trimester is associated with significant increase of maternal blood iron and these increasing levels may be lead to increase the risk of pre-eclampsia in pregnant women.